Prevalence and concentration of pesticides in European waters: A protocol for systematic review and meta-analysis. - Manuel Serrano Valera; Nuria Vela; Grasiela Piuvezam; Francisco Mateo-Ramírez; Isac Davidson Santiago Fernandes Pimenta; Isabel Martínez-Alcalá (PLoS ONE)
There is currently a growing interest in the so-called emerging pollutants, such as pesticides, pharmaceuticals, personal hygiene care products, drugs, etc., whose presence in natural ecosystems is not necessarily recent, but the development in latest years of new and more sensitive methods of analysis has allowed their detection. They can be present in the natural environment, food, and many products of everyday origin, which suggests that human exposure to them is massive and universal. Therefore, the study of this type of substances is becoming one of the priority lines of research of the main agencies dedicated to the protection of public and environmental health, such as the World Health Organization (WHO), United States Environmental Protection Agency (USEPA) or European Union (EU). In this sense, it is of vital importance to know the nature and quantity of this type of contaminants, to establish preventive mechanisms that minimize its presence in aquatic systems, with special requirements for human consumption. This study aimed to describe a protocol for a systematic review and meta-analysis to assess the status of pesticides in European waters. We will search for original studies in the PubMed/Medline, Scopus, Web of Science, EMBASE, ScienceDirect databases. Prevalence studies of emerging contaminants (pesticides) in water resources (watersheds, aquifers, rivers, marine and springs), wastewaters (influent and effluent), and drinking water should be included. Two reviewers will independently screen and assess the included studies, with any disagreements being resolved by a third reviewer. We will summarize the findings using a narrative approach and, if possible, conduct a quantitative synthesis (meta-analysis). We will conduct the protocol following the Preferred Reporting Items for Systematic Review and Meta-Analyses Protocols (PRISMA-P) guidelines. The review will summarize the current evidence on the presence of pesticides in European waters such as glyphosate, chlorpyrifos, pyrethroid pesticides, neonicotinoid pesticides, and/or fungicides, in samples of different water resources like wastewaters and drinking water. We expect that this systematic review will establish preventive mechanisms that minimize the presence of pesticides in water in the environment.